1987
DOI: 10.1002/j.1460-2075.1987.tb02351.x
|View full text |Cite
|
Sign up to set email alerts
|

Clovers secrete specific phenolic compounds which either stimulate or repress nod gene expression in Rhizobium trifolii

Abstract: Rhizobium tifolii mutants containing Escherichia coli lac gene fusions to specific nodulation (nod) genes were used to characterise phenolic compounds secreted from the roots of white clover (Trifolium repens) plants. These compounds either had stimulatory or inhibitory effects upon the induction of the nod genes. The stimulatory compounds were hydroxylated flavones and the most active compound was 7,4'-dihydroxyflavone. The inhibitory compounds present in white clover root exudates were umbelliferone (a couma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
125
3
6

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 230 publications
(140 citation statements)
references
References 28 publications
6
125
3
6
Order By: Relevance
“…Studies with compounds not exuded by the host legume have shown that weak nod gene inducers can restrict the activity of strong inducers in Rhizobium leguminosarum biovar viciae (6), R. leguminosarum biovar trifolii (4), and in R. meliloti (18,19). Other commercially available flavonoids without detectable nod gene-inducing activity inhibited activities of strong nod gene inducers in several systems (4,6,18). In one case, formononetin and umbelliferone, compounds with no nod gene-inducing activity, were identified in clover root extracts (20) and shown to inhibit nod gene induction by 4',7-dihydroxyflavone in R. leguminosarum biovar trifolii (4).…”
mentioning
confidence: 99%
“…Studies with compounds not exuded by the host legume have shown that weak nod gene inducers can restrict the activity of strong inducers in Rhizobium leguminosarum biovar viciae (6), R. leguminosarum biovar trifolii (4), and in R. meliloti (18,19). Other commercially available flavonoids without detectable nod gene-inducing activity inhibited activities of strong nod gene inducers in several systems (4,6,18). In one case, formononetin and umbelliferone, compounds with no nod gene-inducing activity, were identified in clover root extracts (20) and shown to inhibit nod gene induction by 4',7-dihydroxyflavone in R. leguminosarum biovar trifolii (4).…”
mentioning
confidence: 99%
“…One observation that has been consistent among independent laboratories is that the root tip is rich in chemicals that specifically influence reporter gene expression (Firmin et al, 1986;Redmond et al, 1986;Djordjevic et al, 1987;Peters and Long, 1988). Because this region of intense activity corresponds with some precision to the region where border cells are released, it was of interest to test the hypothesis that border cells constitute one cellular source of signals that induce microbial gene expression.…”
Section: Discussionmentioning
confidence: 92%
“…Even allowing for loss of some root tip exudate by diffusion into the agar or absorption into paper, the amount from border cells alone could easily account for a significant part of the intense reporter gene activity that occurs at root tips of legumes (Firmin et al, 1986;Redmond et al, 1986;Djordjevic et al, 1987;Peters and Long, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations